Chapter Adult Education Policies and Sustainable Development in Poland and Portugal: A Comparative Analysis of Policies and Practices - Guimarães, Paula (Studies on Adult Learning and Education, 2020)
Education for sustainable development is presently a relevant topic in the policies of international organisations (such as UN/UNESCO and the European Union) and in national contexts such as Poland and Portugal. Within the policies implemented, civil society organisations and social movements undertake (adult) education for sustainable development projects and activities that have an important impact by raising awareness and promoting changes in the behaviour and attitudes of both countries' populations. However, several challenges can be pointed out regarding the implementation of these initiatives. These challenges will be highlighted in this article, which focuses on the comparison of policies and practices implemented in Poland and Portugal.